Prasugrel pharmacokinetics and pharmacodynamics in subjects with moderate renal impairment and end-stage renal disease. - Small DS; Wrishko RE; Ernest CS II; Ni L; Winters KJ; Farid NA; Li YG; Brandt JT; Salazar DE; Borel AG; Kles KA; Payne CD (Journal of Clinical Pharmacy & Therapeutics, 2009)
Objective: The pharmacokinetic (PK) and pharmacodynamic (PD) responses to prasugrel were compared in three studies of healthy subjects vs. those with moderate or end-stage renal impairment. Methods: Two of the three protocols were parallel-design, open-label, single dose (60-mg prasugrel) studies in subjects with end-stage renal disease (ESRD; n = 12) or moderate renal impairment ( n = 10) and matched healthy subjects with normal renal function ( n = 10). The third protocol was an open-label, single-dose escalation (5, 10, 30 and 60 mg prasugrel) study in subjects with ESRD ( n = 16) and matched healthy subjects with normal renal function ( n = 16). Plasma concentrations of prasugrel's active metabolite were determined and pharmacokinetic parameter estimates were derived. Maximum platelet aggregation (MPA) was measured by light transmission aggregometry using 20 [mu]m adenosine diphosphate as agonist. Results: Across all studies, prasugrel's Cmax and AUC0- t were 51% and 42% lower in subjects with ESRD than in healthy subjects. AUC0- t did not differ between healthy subjects and subjects with moderate renal impairment. The magnitude of change and time-course profiles of MPA was similar for healthy subjects compared with subjects with moderate renal impairment and those with ESRD. Prasugrel was well-tolerated in all subjects. Conclusion: There was no difference in pharmacokinetics or PD responses between subjects with moderate renal impairment and healthy subjects. Despite significantly lower exposure to prasugrel's active metabolite in subjects with ESRD, MPA did not differ between healthy subjects and those with ESRD.